Gestão de bibliotecas e serviços de informação: estratégias para retenção de usuários - Lemõns, Alessandra Isnardi (My University, 2026)
Contemporary transformations in the production, circulation and use of information, intensified by the expansion of digital technologies, have redefined the role of libraries as service organizations in the knowledge economy. In this scenario, there is a reduction in the frequency of users in physical spaces, concomitantly with the growth in the use of digital platforms and social networks as informational sources, often devoid of scientific validation. Therefore, the need to strategically reposition libraries as central agents in the mediation, qualification and promotion of access to reliable information is reinforced. The general objective of this study was to understand the causes of the reduction in the frequency of users in libraries, considering the social, technological and cultural transformations that impact the use of information services, as well as to propose strategic actions that contribute to the dynamization of these spaces, expanding their access, relevance and engagement with the community. The research, with a qualitative approach, used two focus groups as data collection techniques: one composed of eight civil servants and the other of nine students. This strategy enabled an in-depth understanding of the perceptions, experiences, and expectations of this specific audience. The results showed that user retention is a multidimensional phenomenon, influenced by structural, communicational, digital and managerial factors. Challenges related to updating the collection, infrastructure limitations, and barriers to accessing digital resources stand out. On the other hand, the quality of the service and the academic potential of the library emerge as strategic elements for its institutional valorization. From the theoretical and managerial contributions, the study reinforces the need for an integrated management, oriented to the user experience, which articulates the development of collections, communication and marketing strategies, training in informational skills and reconfiguration of physical spaces. We show that the library should be understood as a strategic component of the academic infrastructure, whose strengthening is directly related to student permanence, the quality of training and the fulfillment of the institutional mission. [resumo fornecido pelo autor]
As transformações contemporâneas na produção, circulação e uso da informação, intensificadas pela expansão das tecnologias digitais, têm redefinido o papel das bibliotecas enquanto organizações de serviços na economia do conhecimento. Nesse cenário, observa-se a redução da frequência de usuários em espaços físicos, concomitantemente ao crescimento do uso de plataformas digitais e redes sociais como fontes informacionais, muitas vezes desprovidas de validação científica. Diante disso, reforça-se a necessidade de reposicionar estrategicamente as bibliotecas como agentes centrais na mediação, qualificação e promoção do acesso à informação confiável. O estudo teve como objetivo geral compreender as causas da redução da frequência de usuários nas bibliotecas, considerando as transformações sociais, tecnológicas e culturais que impactam o uso dos serviços de informação, bem como propor ações estratégicas que contribuam para a dinamização desses espaços, ampliando seu acesso, relevância e engajamento junto à comunidade. A pesquisa, de abordagem qualitativa, utilizou como técnica de coleta de dados dois grupos focais: um composto por oito servidores e outro por nove estudantes. Essa estratégia possibilitou uma compreensão aprofundada das percepções, experiências e expectativas desse público específico. Os resultados evidenciaram que a retenção de usuários constitui um fenômeno multidimensional, influenciado por fatores estruturais, comunicacionais, digitais e gerenciais. Destacam-se desafios relacionados à atualização do acervo, limitações de infraestrutura e barreiras no acesso a recursos digitais. Em contrapartida, a qualidade do atendimento e o potencial acadêmico da biblioteca emergem como elementos estratégicos para sua valorização institucional. A partir das contribuições teóricas e gerenciais, o estudo reforça a necessidade de uma gestão integrada, orientada à experiência do usuário, que articule o desenvolvimento de coleções, estratégias de comunicação e marketing, capacitação em competências informacionais e reconfiguração dos espaços físicos. Evidenciamos que a Biblioteca deve ser compreendida como um componente estratégico da infraestrutura acadêmica, cujo fortalecimento está diretamente relacionado à permanência estudantil, à qualidade da formação e ao cumprimento da missão institucional. [resumo fornecido pelo autor]
Keywords: Bibliotecas - Administração; Biblioteconomia; Library - Management; Library science